Skin clinical and morphological changes in patients with seborrheic keratosis - Bondar, O. (Journal of Education, Health and Sport, 2025)
The clinical characteristics and morphological features of seborrheic keratosis in 30 patients are presented. In 26 (86.7%) cases, the process was localized only on the covered areas of the skin (back, chest, shoulders), and in 4 (13.3%) cases, it affected the face and neck. The average number of lesions per patient was 6.5±2.1, with an average size of the largest diameter measuring 1.7±0.6 cm. Morphologically, seborrheic keratosis was manifested in various histological variants (hyperkeratotic, acanthotic, "irritated", mixed), acanthosis, epidermal cell proliferation, primarily of basal cells, as well as the presence of keratin cysts, circulatory disturbances, and immune cell reactions of varying intensity.